Features of clinical and radiological characteristics of the area of consolidated fracture after osteosynthesis by means of biodegradable polymer polyglycolide implants in long terms - Dudko, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To determine clinical and radiological changes, peculiarities of CT and MRI images of the area of consolidated fracture after osteosynthesis by means of biodegradable polymer of polyglycolide implants in long terms. Methods: Outcomes of treatment in 37 patients within 6–30 years with using of clinical and instrumental (radiography, MRI, CT) methods. Results: In patients in 30 years after surgeries there were no pain or other discomfort felings, acute inflammation in the area of polyglycolide implantation. Limb function and overall condition of patients were satisfactory. Radiologically in long terms there was defined formation of a distinct trabecular bone structure in the area of implementation of polyglycolic fixateur. During MRI examination distinct bone structure without any pathological formations was detected. Manifestations of local swelling and inflammation in the area of implantation, as well as thickening of the joint capsule, excess fluid, signs of inflammation in the joint and surrounding tissues have been not identified. Age-related degenerative changes were similar on contralateral and operated limb. During CT it was determined that the density and structure of bone tissue at the implantation site of the polyglycolide fixateur was not significantly different from that one in the contralateral limb. Conclusions: It was found that within 30 years after implantation of fixateurs made of polyglycolide processes of bone tissue regeneration are not violated, and pathological formations in bone and soft tissues are not formed. Polyglycolide and products of its biodegradation do not lead to the development or enhancement of degenerative processes in joints of the operated limb for a long period of observation. The results of applying of investigated fixateurs are not inferior to foreign analogues «Biofix», «Lactosorb», «Activascrew».